PENGARUH MODIFIKASI BOLA VOLI MENGGUNAKAN BOLA PLASTIK TERHADAP PENINGKATAN MINAT BELAJAR PADA SISWI KELAS VIII PUTRI MTS ISLAMIYAH BALEN BOJONEGORO - Benny Widya Priadana; Sunu Wahyudhi; Muhammad Zamroni Hanif (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2017)
The study began with the maximal student learning outcomes in volleyball learning materials. The purpose of this study was to determine the learning outcomes of volleyball games through the modification of volleyball games to the interests of eighth grade female students at MTs Islamiyah Balen Bojonegoro. This research is a classroom action research study consisting of 2 cycles, each cycle having 2 meetings. Each face-to-face meeting lasts 2 hours or 2 x 40 minutes (80 minutes). The research sample was all students of class VIII Putri MTs Islamiyah Balen Bojonegoro Academic Year 2017, totaling 66 students. Data collection methods used in this study used a questionnaire / questionnaire, while the data analysis researchers used descriptive analysis of percentages.The results showed that the interest of VIII grade female students at MTs Islamiyah Balen Bojonegoro after learning to use volleyball game modifications had increased. This can be seen from the aspect of interest that originally increased by 43.3% to 68%, while the aspect of attention that was originally 42.8% to 66.1%, and the aspect of the activity which was originally 43.5% to 67.6%. So it can be concluded that the interest of students towards physical education learning by using a volleyball game modification in class VIII Putri MTs Islamiyah Balen students in 2017 academic year in the high category.